Aerodynamic performances of rounded fastback vehicle. (August 2017) - Rossitto, Giacomo; Sicot, Christophe; Ferrand, Valérie; Borée, Jacques; Harambat, Fabien
Experimental and numerical analyzes were performed to investigate the aerodynamic performances of a realistic vehicle with a different afterbody rounding. This afterbody rounding resulted in a reduction to drag and lift at a yaw angle of zero, while the crosswind performances were degraded. Rounding the side pillars generated moderate changes to the drag and also caused important lift reductions. A minor effect on the drag force was found to result from the opposite drag effects on the slanted and vertical surfaces. The vorticity distribution in the near wake was also analyzed to understand the flow field modifications due to the afterbody rounding. Crosswind sensitivity was investigated to complete the analysis of the aerodynamic performances of the rounded edges models. Additional tests were conducted with geometry modifications as spoilers and underbody diffusers.